INVESTMENT ATTRACTIVENESS OF UKRAINE: THE MAIN PROBLEMS AND THE WAYS OF THEIR SOLUTIONS - Новікова , Тетяна; Гайдар , Ірина (Socio-economic relations in the digital society, 2019)
In this article such concepts as «investment climate», «investment attractiveness» are investigated, the essence of definitions and their diff erence are investigated. Also in this paper are indicators of investment attractiveness, attention is drawn to the main problems and ways to solve them. The essence of the factors that directly influence the development of the investment environment of the state has been studied and analyzed. Prospects for the growth of investment in the country are determined.